2021
DOI: 10.1073/pnas.2109269118
|View full text |Cite
|
Sign up to set email alerts
|

Local accumbens in vivo imaging during deep brain stimulation reveals a strategy-dependent amelioration of hedonic feeding

Abstract: Impulsive overeating is a common, disabling feature of eating disorders. Both continuous deep brain stimulation (DBS) and responsive DBS, which limits current delivery to pathological brain states, have emerged as potential therapies. We used in vivo fiber photometry in wild-type, Drd1-cre, and A2a-cre mice to 1) assay subtype-specific medium spiny neuron (MSN) activity of the nucleus accumbens (NAc) during hedonic feeding of high-fat food, and 2) examine DBS strategy-specific effects on NAc activity. D1, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Perhaps, the neuropeptides released by PSTN Tac1 neurons cause a sustained change in neural activity in downstream neural populations. Indeed, many other neural populations that affect food intake behavior also show a transient increase in neural activity on the timescale of seconds ( Berrios et al, 2021 ; Luskin et al, 2021 ; Mohammad et al, 2021 ; Wu et al, 2022 ). Alternatively, perhaps PSTN Tac1 neurons exhibit a transient increase in activity but do not completely return to baseline levels over a sustained period in a way that is not detectable by fiber photometry.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, the neuropeptides released by PSTN Tac1 neurons cause a sustained change in neural activity in downstream neural populations. Indeed, many other neural populations that affect food intake behavior also show a transient increase in neural activity on the timescale of seconds ( Berrios et al, 2021 ; Luskin et al, 2021 ; Mohammad et al, 2021 ; Wu et al, 2022 ). Alternatively, perhaps PSTN Tac1 neurons exhibit a transient increase in activity but do not completely return to baseline levels over a sustained period in a way that is not detectable by fiber photometry.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the network effect of DBS, Paulk et al mapped the cortical responses evoked by single-pulse electrical stimulation delivered via intracranial electrodes in epilepsy patients and confirmed that DBS evoked broad network responses that were stimulation location and pulse parameter dependent 26 . Finally, using cellular fluorescent calcium imaging techniques, a couple of recent studies in animal models demonstrated that DBS altered the relationship of intracellular calcium dynamics and behavior, supporting a network effect of DBS [27][28][29] .…”
mentioning
confidence: 90%
“…In both of these methods, there are issues concerning detection sensitivity and selectivity of neurotransmitters, molecular inaccuracy or, for instance, the impossibility to target electrochemically inert s ubstances, such as glutamate, or to conduct chronic (e.g., 2–6 weeks) studies. So far, a single fiber photometric study has explored the mediated DBS effects integrating photometric readouts, although stimulating and recording directly in the NAc in the context of a model of eating disorders [ 42 ], hence also showing the novelty of this technique to elucidate DBS mechanisms in an electrical artifact free recording platform.…”
Section: Discussionmentioning
confidence: 99%